Trends in new species discovery of Orthoptera (Insecta) from Southeast Asia - Tan, Ming Kai; Choi, Jihea; Shankar, Nivedita (Zootaxa, 2017)
The orthopterans are diverse insects and play important roles in the ecosystem as well as having “love-hate relationship” with humans. Documentation of diversity in Southeast Asia has long history but remains incomplete. Using information of type specimens and Geographic Information System (GIS) techniques, we investigated the following questions on new species discovery for the region, specifically: (1) How are new species discoveries of orthopterans distributed in Southeast Asia? (2) How have new species discoveries changed with time? (3) How do new species discoveries relate to the countries of the type depositories? We found that new species discoveries, relative to sampling, are fragmentary in Southeast Asia and changes with different time periods. We also find type depositories tightly linked to the human (colonial) history of Southeast Asian countries. We provide some recommendations and hope that this can help to accelerate the study of orthopteran diversity in the region.